Mineral composition and paragenesis of altered and mineralized zones in the Gadir low sulfidation epithermal deposit (Lesser Caucasus, Azerbaijan) - Novruzov, Novruz; Valiyev, Anar; Bayramov, Aydin; Ibrahimov, Javid; Mammadov, Sabuhi; Ebdulrehimli, Aygul (IJES, 2019)
Mineralogy, gold mineralization and metal contents of the Gadir deposit have been investigated during current research in order to determine the geological conditions, temporal and spatial relationship with certain mineral assemblages and associations. The mineralogy of ore bodies is mainly composed of pyrite, chalcopyrite, sphalerite, galena, petsite, native gold, electrum and subordinate molybdenite. Gold is hosted by pyrite and chalcopyrite minerals in fracture-filling textures and forms a thin dispersion condition. The native gold was observed in chalcopyrite, whichis probably related to the second stage of ore deposition. The Gadir deposit can be classified to Au-Ag-Cu-Zn±Pb stockwork-type mineralization which is characteristic of low sulfidation epithermal deposit.
Keywords: Hydrothermal alteration -- Azerbaijan.; Ore mineralogy -- Azerbaijan.; Gold mineralization -- Azerbaijan.